Tinjauan Yuridis terhadap Pencabulan Anak dibawah Umur Putusan Nomor 666/Pid.Sus/2023/PN. SRG - Setiawanti, Via Mutiara; Hasuri, Hasuri (Wajah Hukum, 2025)
The increasing crime rate in Indonesia has resulted in the emergence of various modus operandi in the occurrence of criminal acts, one of which is the abuse of minors. Child abuse can damage family life, the school environment, and even indirectly threaten the future of children who are the next generation of the Indonesian nation. The purpose of this study is to analyze the factors that cause the occurrence of criminal acts of child molestation in Serang Regency, Banten Province. This study uses primary data obtained from direct interviews with informants at the Class II Serang Prison, Banten. The conclusion of this study shows the factors causing the occurrence of child molestation from a criminal law perspective. The application of the law to perpetrators of criminal acts of child molestation is carried out by providing sanctions in accordance with Law Number 23 of 2002 concerning Child Protection, such as imprisonment or criminal penalties.